Evaluating pharmacokinetic drug–drug interactions of direct oral anticoagulants in patients with renal dysfunction. (4th March 2022) - Hanigan, Sarah; Park, Jeong M.
ABSTRACT: Introduction: Drug transporters, metabolic enzymes, and renal clearance play significant roles in the pharmacokinetics of direct oral anticoagulants (DOACs). Recommendations for DOAC drug–drug interactions (DDIs) by the product labeling are limited to selected CYP3A4 and P-glycoprotein inhibitors and lack considerations for concomitant renal dysfunction. Areas covered: This review focuses on: 1) current recommendations for the management of pharmacokinetic DOAC DDIs and the evidence used to support them; 2) alterations in DOAC exposure in the setting of concomitant DDIs and mild, moderate, and severe renal impairment; 3) clinical outcomes associated with this combination; and 4) expert recommendations for the management of pharmacokinetic DOAC DDIs. English-language, full-text articles on apixaban, dabigatran, rivaroxaban, and edoxaban with a publication date up to 30 September 2021 were retrieved from PubMed. Expert opinion: Given the lack of supporting clinical data, empiric dose adjustments based on pharmacokinetic data alone should be avoided. When a considerable increase in a DOAC exposure is anticipated, it may be advisable to use an alternative DOAC or anticoagulant from a different class. Future research on identification of DOAC therapeutic ranges and target patient populations is needed to inform clinical utility of DOAC level monitoring to guide the management of DDIs.